2020
DOI: 10.1038/s41419-020-2294-6
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of CYLD phosphorylation as a novel therapeutic approach for adult T-cell leukemia/lymphoma (ATLL)

Abstract: Adult T-cell leukemia/lymphoma (ATLL) is a malignancy of mature T cells associated with chronic infection by human T-cell lymphotropic virus type-1 (HTLV-1). ATLL patients with aggressive subtypes have dismal outcomes. We demonstrate that ATLL cells co-opt an early checkpoint within the tumor necrosis factor receptor 1 (TNFR1) pathway, resulting in survival advantage. This early checkpoint revolves around an interaction between the deubiquitinase CYLD and its target RIPK1. The status of RIPK1 K63-ubiquitinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…In lymphoma like CLL, CYLD protein expression levels was lower in tumor invasive lymph node than in normal lymph node samples [ 49 ]. But in our previous research about T cell lymphoma,total CYLD protein expression levels was no significant difference between tumor invasive lymph node and normal lymph node samples [ 24 ]. These findings suggest that there are different mechanisms of functional regulation of CYLD in different tumors.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In lymphoma like CLL, CYLD protein expression levels was lower in tumor invasive lymph node than in normal lymph node samples [ 49 ]. But in our previous research about T cell lymphoma,total CYLD protein expression levels was no significant difference between tumor invasive lymph node and normal lymph node samples [ 24 ]. These findings suggest that there are different mechanisms of functional regulation of CYLD in different tumors.…”
Section: Discussionmentioning
confidence: 97%
“…The research on how CYLD phosphorylation regulate the occurrence and development of hematological malignances is still lacking. Our previous study indicated high protein expression levels of CYLD phosphorylation in adult T-cell leukemia/lymphoma (ATLL) and regulating CYLD phosphorylation could regulate CYLD ubiquitin activity to improve ATLL cells apoptosis [ 24 ]. Whether CYLD phosphorylation is also a regulator for non-GCB-DLBCL apoptosis needs further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both IKK inhibitors and overexpression of kinase-inactive TBK/IKK can lower CYLD phosphorylation and trigger cell death ( Table 3 ). These results indicated that phosphorylated CYLD is a crucial regulator of ATLL survival and a potential novel therapeutic target for pharmacologic modification in ATLL ( Xu et al, 2020 ).…”
Section: The Therapeutic Potential Of Targeting Ptms In Dubsmentioning
confidence: 88%
“…The loss of CYLD stabilizes the TNFR1 complex and NF-κB activity and consequently suppresses TNFα-induced cell death [128][129][130][131][208][209][210]. In TNFR1 signaling, IKK-mediated phosphorylation at serine 418 of CYLD protects cancer cells against cell death by downregulating CYLD activity [211][212][213]. In addition to NF-κB regulation, CYLD promotes cell death by promoting RIPK1 activity.…”
Section: Cyldmentioning
confidence: 99%